Becoming a Baby Friendly Hospital. Issue 1 (January 2017) - Tran, Andrea
Abstract : Abstract: The purpose of the Baby-Friendly hospital initiative is to encourage hospitals to use best practices to support infant feeding, as demonstrated by implementing the Ten Steps to Successful Breastfeeding recommended by the World Health Organization. The journey to becoming a Baby-Friendly designated hospital is challenging but ultimately rewarding. In October 2015, Boulder Community Foothills Hospital, a community hospital with a strong breastfeeding culture and a 98% rate of women who initiate breastfeeding postpartum, became one of the approximately 300 Baby-Friendly designated hospitals in the United States. Significant challenges and how we succeeded each step of the way are included. Even when a hospital is breastfeeding friendly, becoming Baby-Friendly is never a mere formality. Nursing leadership teams in other hospitals may find value in the details of our successful efforts to become a Baby-Friendly designated hospital. Abstract : The journey to Baby Friendly designation can be challenging, but ultimately rewarding in supporting a hospital culture that promotes successful breastfeeding. One hospital's path to Baby Friendly is detailed. Others considering this designation may find details of their experience valuable.